A gene signature associated with prognosis and immune processes in head and neck squamous cell carcinoma. Issue 8 (6th March 2019) - Bai, Shuang; Zhang, Ping; Zhang, Jian‐Cheng; Shen, Jun; Xiang, Xu; Yan, Ying‐Bin; Xu, Zhen‐Qi; Zhang, Jun; Long, Li; Wang, Chao; Shi, Ping; Yang, Li; et al.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) has a poor prognosis that has not significantly improved in the past several decades. A prognostic‐related signature was needed. Methods: The Cancer Genome Atlas and GSE41613 databases were downloaded as a training and validation set, respectively. We identified 12 genes that demonstrated progression and prognostic value, and then, a gene signature was constructed. Results: This classification could reflect distinct characteristics, phenotypically and molecularly, among HNSCC tumors. It could stratify patients with significantly different survival rates (median survival: 2083 days vs 927 days; P = 3.85E‐08) in the training cohort and validation cohort ( P = 0.007) and was significantly involved in immune/inflammatory response and tumor progression processes. Conclusions: This bioinformatics‐based signature suggested the presence of two distinct populations of patients with HNSCC with distinguishable phenotypic characteristics and clinical outcomes and might provide insight for new types of immune therapy.